2022
DOI: 10.1088/1755-1315/951/1/012100
|View full text |Cite
|
Sign up to set email alerts
|

The use of near-infrared reflectance spectroscopy (NIRS) to predict dairy fibre feeds in vitro digestibility

Abstract: Information on dairy fibre feed digestibility is important in ration formulation to better predict dairy cattle performance. However, its measurement takes time. Near-infrared reflectance spectroscopy (NIRS) is a rapid, precise, and cost-effective method to predict nutrient value, such as chemical content and digestibility of feedstuffs. This study aims to develop a database for an in vitro digestibility prediction model using NIRS, including dry matter digestibility (DMD), neutral and acid detergent fibre dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
1
8
1
Order By: Relevance
“…On the other hand, the model developed for palmitic, linolenic, and eicosenoic acids were moderately suitable with R 2 value of 0.68, 0.77, and 0.74 respectively. These were in agreement to NIRS models developed for tryptophan in maize 30 and fibers in feeds 23 that reported by Escuredo et al 31 The RPD C values of calibration equations developed for oil, palmitic, stearic, oleic, linoleic, and erucic acids are more than two as shown in Table 2, which were acceptable result in the good range as studied by Aldo et al 32 Furthermore, the RPD C values for palmitic, linolenic, and eicosenoic acid were 1.6, 1.8, and 1.7, respectively, which were lower than the other equations but still adequate for screening, according to Khamchum et al 33 RER values of all equation of this study varied from 10.0 to 23.0 which agreed with the recommended values for screening purposes as reported by Yang et al 10 except models developed for palmitic, linolenic, and eicosenoic acid.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…On the other hand, the model developed for palmitic, linolenic, and eicosenoic acids were moderately suitable with R 2 value of 0.68, 0.77, and 0.74 respectively. These were in agreement to NIRS models developed for tryptophan in maize 30 and fibers in feeds 23 that reported by Escuredo et al 31 The RPD C values of calibration equations developed for oil, palmitic, stearic, oleic, linoleic, and erucic acids are more than two as shown in Table 2, which were acceptable result in the good range as studied by Aldo et al 32 Furthermore, the RPD C values for palmitic, linolenic, and eicosenoic acid were 1.6, 1.8, and 1.7, respectively, which were lower than the other equations but still adequate for screening, according to Khamchum et al 33 RER values of all equation of this study varied from 10.0 to 23.0 which agreed with the recommended values for screening purposes as reported by Yang et al 10 except models developed for palmitic, linolenic, and eicosenoic acid.…”
Section: Resultssupporting
confidence: 84%
“…However, palmitic, stearic, and eicosenoic acid had a coefficient of determination of prediction models (R 2 v) of 0.02, 0.0.04, and 0.3, respectively, which indicated that the reference and NIRS value were not correlated and they were the bad equations. Furthermore, according to Murphy et al 35 and Zahera, 23 the RPDv values of these models were less than the required value of 1.5. In addition, models developed for palmitic, stearic acid, and eicosenoic acid had narrow distribution datasets and showed a poor correlation between reference values and NIRS predicted values.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…NIRS has been used to estimate the ‘conventional’ nutrient composition (e.g., crude protein, neutral detergent fiber, etc.) [ 21 ] of feed, but it has also proven useful to predict concentrations of compounds such as tannins and non-starch polysaccharides [ 22 , 23 ], or to predict properties of a feed, such as digestibility or rumen degradability, which are observed after a feed is offered to animals [ 23 , 24 , 25 ]. NIRS has also shown a potential to estimate the yield of CH 4 from biomass digestors for biogas production [ 26 , 27 ] and has been successful in predictions of CH 4 production during rumen batch culture fermentation with over 100 forage species [ 28 ].…”
Section: Introductionmentioning
confidence: 99%